Pengalaman Mekanisme Koping Perawat Pelaksana IGD yang Mengalami Stres Kerja - Rahmat Ali Putra Harahap; Setiawan Setiawan; Roymond H. Simamora (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to explore the experiences of nurses and identify coping strategies used to overcome the problems they face. The research design used is descriptive phenomenology. The results of the study were 5 themes, the researchers identified five, namely: 1) Sources of work stress for nurses in the emergency unit, 2) doing other activities for various work themes, 3) Coping with stress by improving self-ability, 4) performing various constructive coping techniques, and 5) Make routine work stress handling activities for nurses. In conclusion, the average nurse uses problem-focused coping strategies and to deal with work stress. Keywords: Coping mechanism, Experience, Emergency Room Nurse, Job Stress